A construção dos escândalos de corrupção: repertórios interpretativos das revistas Veja e Carta Capital sobre a Operação Lava-Jato - Gomes, Túlio Gonçalves (2016)
Corruption is a transgression that has been highlighted in the Brazilian media. Present essentially in the political environment, it drags among several other sectors, emerging behind-the-scenes, in schemes involving collusions and secrets. In order to the corruption becomes a scandal, it’s necessary that this transgression should be brought to the public attention, and that is the media role. In the year of 2014, the Lava Jato operation was launched by the Federal Police, which is already considered the largest anti-corruption operation of all times, in Brazil. The investigations began with focus on a group of dollars exchangers, and later, it was discovered a scheme public money deviation installed inside the largest Brazilian state-owned company, Petrobras, becoming a scandal. When the national and international media made the scandal public, this came with many implications for the society, individuals and involved organizations. Recognizing that the corruption sociology and the scandals sociology are intertwined, we have established as a general objective of this dissertation to identify and analyze discursively the interpretive repertories of the media over the corruption scandals in the Lava Jato Operation case, in the first year after its outbreak. At first, we present theoretical concepts and perspectives about corruption issues and the components of the scandals. Then, through a documentary research, we selected 114 articles to be analyzed in the two chosen medias, being them the weekly circulation magazines: “Veja” and “Carta Capital”. In order to operationalize the research, we were guided by three questions: (1) what interpretive repertories about corruption are used by the media to report study cases? (2) What theoretical perspectives about corruption emerge on the media speeches? (3) Do the corruption implications schemes emerge on the speeches? If so, in what way do they manifest? The results led to the identification of three main interpretive repertoires in each magazine, which reinforce the difference of position between the two ones. The repertoires used by “Veja magazine” were in opposition to the government party at the time, the PT; and the “Carta Capital magazine” repertoires sought to demonstrate that corruption is a general problem of all political parties, and that the media should only inform the reader, and not try to influence in favor of one or another political party.